Strength and water absorption rate of concrete made from palm oil fuel ash - Manap, Norpadzlihatun; Muhamad, Nor Izzah; Sandirasegaran, Kavitha (Trans Tech Publications, 2017)
Concrete is one of the most important materials for construction industry. The material in the mixture of concrete includes cement, sand and coarse aggregate. Production of cement causes the air pollution from the emission of carbon dioxide to the air. This research studies the replacement of cement with palm oil fuel ash (POFA) in the concrete mixture. The objective of this research is to investigate the compressive strength of concrete and water absorption rate of concrete made from POFA and to compare the strength and absorption rate between conventional concrete and concrete made from POFA. This is to indicate whether the compressive strength and absorption rate are equivalent to the strength of conventional concrete. The methodology used in this research is experimental method and the palm oil fuel ash was taken from palm oil mill in Cha’ah, Johor, Malaysia. The results of this research are the specimens which contain 20% POFA has a compressive strength and water absorption rate comparable to conventional concrete.